Prescription strategy of antimalarials in cutaneous and systemic lupus erythematosus: an international survey. (May 2021) - Petitdemange, Arthur; Felten, Renaud; Sibilia, Jean; Martin, Thierry; Arnaud, Laurent
Background: Antimalarial agents (AMs), mainly hydroxychloroquine (HCQ) and chloroquine, are the cornerstone of treatment of cutaneous and systemic lupus erythematosus. However, many aspects of AM prescription remain empirical. The aim of this study was to assess the modalities of AM prescription among physicians treating patients with lupus and to verify the assumption that AM use is heterogeneous and frequently at variance with international guidelines. Methods: We performed an international cross-sectional study among physicians involved in lupus care, using a web-based survey (from September 2019 to July 2020) addressing the main controversial aspects of AM prescription. Results: A total of 298 physicians [median age: 42 (interquartile range: 17) years, mainly internists and rheumatologists] from 35 countries participated to the study. A total of 93% used HCQ as the first-line AM, 69.5% used fixed doses of AMs (mainly 400 mg/day for HCQ) and only 37.9% adjusted the dose in case of renal failure. The main reasons for measuring HCQ blood levels were suspected non-adherence (55.7%) and failure of AM treatment (34.1%). In case of AM failure, 58.0% added an immunosuppressive agent. In case of remission, 49.7% maintained the same dose of AM, whereas 48.3% reduced the dose. One-third of respondents reported not following the American screening guidelines on AM retinal toxicity and 40.9% started retinal screening from the first year of treatment. Conclusion: This study highlights the strong heterogeneity of AM prescription in lupus, as well as several key unmet needs regarding AMs. This may be improved by developing more comprehensive recommendations and favoring dissemination among physicians.